Causal effects of fatty acids on depression: Mendelian randomization study - Zeng, Lingsi; Lv, Honggang; Wang, Xubo; Xue, Ranran; Zhou, Cong; Liu, Xia; Yu, Hao (Frontiers in Nutrition, 2022)
It is widely thought that fatty acids (FA) are involved in the pathophysiological process of depres-sion. However, the causal relationships between FA and depression remain elusive and warrant further research. We aimed to investigate the potential causal relationship between FA (saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA) and the risk of depression using Mendelian randomization (MR) analysis. Large-scale European-based genome-wide association studies (GWASs) summary data related to depression (n=500,199 individuals) and FA levels were obtained separately. MR analysis was performed using the Wald ratio and inverse variance-weighted (IVW) methods, and sensitivity analysis was conducted by the simple mode, weighted mode, weighted median method, and MR-Egger method. We found the causal effects for the levels of oleic acid (OA; OR=1.07, p=5.72×10-4), adrenic acid (OR=0.74, p=1.01×10-3), α-linolenic acid (ALA; OR=2.52, p=1.01×10-3), eicosapentaenoic acid (EPA; OR=0.84, p=3.11×10-3) on depression risk, after Bonferroni correction. The sensitivity analyses indicated similar trends. No causal effect between the levels of SFA and depression risk was ob-served. In summary, our study suggests that adrenic acid and EPA are protective against the risk of depression, while OA and ALA are potential risk factors for depression. Nonetheless, the underly-ing mechanisms that mediate the association between these FAs and depression risk should be in-vestigated in further experiments.